REKONSTRUKSI AKSES DAN KONTROL LAHAN TERHADAP ASET PENGHIDUPAN MASYARAKAT PASCA BENCANA ERUPSI GUNUNGAPI MERAPI 2010 DI KECAMATAN CANGKRINGAN KABUPATEN SLEMAN PROVINSI D.I. YOGYAKARTA - , PETRASA WACANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi Volcano environment is the unity of the space where the components of living creature such as plants, animal and humans, as its main component, interact each other, and Merapi Volcano is the center of it. Merapi Volcano eruption in 2010 caused a great impact in the form of livelihood assets loss such as residential communities, farms, forests, plantations, agricultural land and the presence of human casualties. To see the relationship between the disaster effects of land and livelihood asset of the above problems, the researcher formulated three research questions: (1) how are the characteristics of pyroclastic deposit based on the nature and distribution of sediment, (2) how are the access and control of public lands to livelihood assets before and after the Merapi Volcano eruption in 2010, and (3) how is the reconstruction of the damage and loss of livelihood assets due to Merapi Volcano eruption in 2010. This study conducted in the Cangkringan Sub-district, Sleman Regency in Yogyakarta, aim to (1) assess the characteristics of the hot cloud based on the nature and distribution of pyroclastic deposits, (2) assess of the access and control of public land to livelihood assets, and (3) reconstruct the access and control of land to livelihood assets. This research combined participatory quantitative and qualitative methods. Data collection methodology was conducted through survey and field observations by purposive sampling in 84 observation location of the objects that were directly affected by the Merapi Volcano eruption in 2010of and in-depth interviews sample selection with purposive sampling with a sample population of 53 families who were directly affected by Merapi Volcano eruption in 2010. Data analysis was conducted in qualitative descriptive data gathering based on qualitative and quantitative data. Based on the nature and distribution of pyroclastic deposits, Merapi Volcano hazards of hot clouds are divided into 3 kinds: (1) hot cloud of pyroclastic flows, (2) hot cloud pyroclastic air fall, and (3) hot cloud pyroclastic surge. The access and control of land to livelihood assets is the public access of the right to land ownership and the right to land management, so that the land becomes the important source for the community to fulfill the needs of life, economic, social, shelter and adaptation to overcome the hazards of Merapi Volcano eruption, especially at Merapi Volcano disaster prone areas. According to the results of the reconstruction in Cangkringan Sub-district, the disaster impact was affected by the existence of livelihood assets in the Merapi Volcano disaster prone areas. The researcher divided the two main livelihood zones of the conducted reconstruction (1) farms livelihood zone covers the central and northern zones of Cangkringan Sub-district and, (2) agriculture livelihood zone covers the southern zone of Cangkringan Sub-district.